Effect of sencha (green tea) and silver needle (white tea) addition on the antioxidant activity of probiotic yogurt - Razali, Nor Faizah; Sou, Pui Chia (Penerbit UTHM, 2017)
In this study, antioxidants were extracted from two different types of tea, green tea (Sencha) and white tea (Silver Needle) by using infusion extraction method. The extracted antioxidants were tested with self-made yogurt. The main objectives of this study were to analyze the total phenolic content of the extracted antioxidants from two different types of teas and to observe the shelf life of the self-made yogurt mix when added with the extracted antioxidant. The extracted antioxidants (natural antioxidant) were also compared with the synthetic antioxidant, butylated hydroxyanisole (BHA). In TPC test, the synthetic antioxidant, BHA extract (10103 μg GAE/g ± 0.006403) has the highest content of polyphenol followed by Sencha (8636 μg GAE/g ± 0.03607) and Silver Needle (5787 μg GAE/g ± 0.02759) teas extracts. In DPPH test, the scavenging activity of BHA extract (97.37 % ± 0.001414) was shown the highest values compare to the Sencha (94.03 % ± 0.001414) and Silver Needle (89.78 % ± 0.0389) tea extracts. After the characterization, the extracted antioxidants from Sencha, Silver Needle teas and synthetic antioxidant were incorporated in yogurt as preservatives. The yogurt samples with extracted and synthetic antioxidants were undergone another chemical analysis of yogurt’s lipid which were PV and AOA test. Based on AOA method, the overall of the BHA applied in self-made yogurt shown the highest antioxidant activity value followed by Sencha tea and Silver Needle tea extracts. By using PV method, BHA antioxidant shown the lowest peroxide value followed by Sencha tea and Silver Needle tea extracts. In conclusion, Sencha, Silver Needle teas and BHA were successfully employed to enhance the antioxidant properties of yogurt and provide sustained antioxidants during 28 days of storage.